A study of eutectic temperature of sugar mixture for thermal energy storage - Wisutthimateekorn, Suchanun; Lerkkasemsan, Nuttapol (My University, 2021)
We studied Phase Change Materials (PCMs), which can be used as thermal energy storage for temperatures lower than 120◦C: They can store both sensible heat from a changing temperature and latent heat from changing the state of a substance. The advantage of storing energy in a PCM is that it can be reused continuously, without the degradation of efficiency. Here, the PCM mixture consists of fructose and xylitol and thus, this PCM can be used to store energy below 120◦C. The calculated Excess Gibbs Energy and activity coefficient of xylitol and fructose decreased as the fraction of xylitol increased. We tested a system, which included an evacuated tubular collector and—fructose mixtures. The system with the PCM maintained a water temperature ~14◦C higher than water without the PCM. This PCM system could store 248 kJ/kg. The xylitol—fructose mixture had a market price ~$US 4.62 $/kg (2018 price), so compared to other PCMs, xylitol-fructose was cheap and store energy efficiently.
Keywords: Eutectic temperature; Excess Gibbs Energy; Phase change materials